Langkawi's Ecological and Economic Renaissance: A Study of Blue and Green Opportunities - Ridzuan, Abdul Rahim; Chee Ann, Lim; Md Razak, Mohamad Idham; Akhwan, Muhamad Hafizuddin; Ridzuan, Mardhiyah; Zarin, Nur Izzati (ASEAN Journal on Hospitality and Tourism, 2024)
This article delves into the potential of the blue and green sectors situated in Langkawi Island, Malaysia. With its abundant marine and terrestrial resources, the island needs to strike a balance between its economic growth and environmental preservation imperatives. By leveraging the potential of green and blue sectors such as tourism, fisheries, renewable energy, agriculture, and forestry, Langkawi Island can serve as a model for responsible development, all while preserving its innate natural beauty and biodiversity. A survey was conducted involving 104 local respondents at various attraction points across Langkawi Island to assess the progress of these sectors. Overall, the respondents were predominantly in agreement regarding the impacts of development stemming from both the blue and green economies, coupled with the positive spill-over effects witnessed on the island. The descriptive findings indicate that the potential for growth within these blue and green economies is promising, buoyed by anticipation from both governmental and private sectors. As such, it becomes imperative for policymakers to formulate a comprehensive development plan that can adequately bolster the expansion of these sectors. This preparation will be crucial in ensuring the sustainable growth of Langkawi Island's blue and green economies, ultimately fostering a harmonious coexistence between economic progress and environmental conservation.